Reviews Evaluating Information Technology-Based Cardiac Rehabilitation Programs and Support: A Systematic Review - Mahdieh Arian; Ali Valinejadi; Mohsen Soleimani (Tehran University of Medical Sciences, 2022)
Background: Application of technology in virtual or remote cardiac rehabilitation programs can resolve the challenge of accessing healthcare services and reduce access level inequalities. This study aimed to evaluate the effect of technology on different clinical outcomes in cardiac rehabilitation programs used for cardiovascular (CVD) patients. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses and a comprehensive evidence map of overview was used. Two researchers searched electronic databases such as Science Direct, Medline / PubMed, Web of Science, Scopus, ProQuest, Google Scholar and Cochrane library at the time of publication until Mar 21, 2021. Results: Of 51 reviews published, most of them have reported that the virtual or remote cardiac rehabilitation had a positive effect on most outcomes compared to usual care, and the difference in the type of comparison group and the high heterogeneity in reviews with inconsistent results are due to different technologies used in the interventions, follow-up duration, the type of heart disease, tools, and reporting methods, the quality of the reviews, and the quality of the primary studies included in the reviews. Conclusion: Two important factors before choosing the remote cardiac rehabilitation technology include the complexity of technology and the level of satisfaction and acceptability of the interventions among participants. The simplicity of the interventions increases the acceptability level, and the more complex design and advanced monitoring level during the interventions and the need for specific equipment affect cost saving, so it is important to consider the above cases while choosing the type of technology.